The Communicative Skills Correction Technology of Children with Autistic Spectrum Disorder in the Crimea - Svetlana Motornaya1, Margarita Belenkova1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The communicative skills correction technology in children with autism spectrum disorder is considered. Inthe Crimea centers and funds which provide support and assistance to families raising children with specialdevelopmental features, in particular autism, are being analyzed. The results of a communicative skillscorrection study in children with autism spectrum disorder are presented.